ASSOCIATION OF SMOKING HABIT WITH PERIODONTAL STATUS AMONG ADULT MALE IN RT 19-SEBAPO VILLAGE JAMBI - Linda Marlia; Pahrur Razi; Surayah Surayah; Rendi Astuti (Jurnal Ilmiah Keperawatan Gigi, 2022)
Smoking is a usual habit found among people. The high prevalence of smoking has been taking more attention which in 2018 reached 1,35 billion of people around the world. Smoking also take part as one of periodontal disease risk factors. The aim of this study is to determine the association of smoking habit with periodontal status among adult male in RT 19-Sebapo Village Jambi. This is a cross sectional study with adult male population of 21-60 years old were recruited at RT 19-Sebapo village Jambi. A total of 34 subjects were gathered by total sampling method. A check list chard and CPITN data were collected and analysed. This present study demonstrated that 20 subjects (58,8%) had bad smoking habit along with periodontal disease with deep pocket depth. 14 subjects (41,2%) had light smoking habit along with dental calculus. No association to be found between smoking habit and periodontal status (p-value = 0,34). Oaur suggestion is to improve oral health knowledge especially in periodontal health and to do regular dental check-up for at least once every 6 months at Puskesmas or other dental care center.Keywords: Smoking, Periodontal Status